2016
DOI: 10.1177/1053451216644827
|View full text |Cite
|
Sign up to set email alerts
|

Using Computer-Assisted Instruction to Build Math Fact Fluency

Abstract: Research findings support the use of computer-assisted instruction (CAI) as a curriculum supplement for improving math skills, including math fact fluency. There are a number of websites and mobile applications (i.e., apps) designed to build students' math fact fluency, but the options can become overwhelming. This article provides implementation guidelines to help teachers plan for CAI, including criteria for selecting a program and recommendations for monitoring student progress. In addition, free resources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…The aim of this study is to know about effectiveness of interactive CD learning that had be developed as instructional media in the Basic Network learning process. Instructional media can assist student to understand and apply the learning concepts, so that the learning outcome can be reached by students and instructional media has a big opportunity to close student achievement gap than students do not learn by using instructional media (Wulansari et al, 2017;Keengwe, 2012).The technique that be used in the delivering materials in instructional media effectively can increase phonological awareness in the learning process (Foster, Erickson, Forster, Brinkman, &Torgensen, 1994;Macaruso& Walker, 2008;Mitchell & Fox, 2001;Reitsma&Wesseling, 1998).Instructional media that benefit viewing and hearing are a good way to assist students in the learning process (Woo, 2009).Based on comparing with the old research, there are too much instructional media that had been developed, like development of Computer Assisted Instruction (CAI) in the English course (Keengwe, 2012) and development of Computer Assisted Instruction on the Math course (Hawkins, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study is to know about effectiveness of interactive CD learning that had be developed as instructional media in the Basic Network learning process. Instructional media can assist student to understand and apply the learning concepts, so that the learning outcome can be reached by students and instructional media has a big opportunity to close student achievement gap than students do not learn by using instructional media (Wulansari et al, 2017;Keengwe, 2012).The technique that be used in the delivering materials in instructional media effectively can increase phonological awareness in the learning process (Foster, Erickson, Forster, Brinkman, &Torgensen, 1994;Macaruso& Walker, 2008;Mitchell & Fox, 2001;Reitsma&Wesseling, 1998).Instructional media that benefit viewing and hearing are a good way to assist students in the learning process (Woo, 2009).Based on comparing with the old research, there are too much instructional media that had been developed, like development of Computer Assisted Instruction (CAI) in the English course (Keengwe, 2012) and development of Computer Assisted Instruction on the Math course (Hawkins, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, the results revealed that students' perceptions about classroom technology and facilities could influence their STEM college learning and career orientation. To enhance students' STEM college learning and career orientation, STEM teachers are advised to maintain a technology-assisted learning environment by working with school administrators (Hawkins et al, 2017). Students' learning is enhanced due to the multiple learning functions and interactive learning environments provided by using technology in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, effective fluency-building instruction should incorporate modeling (Codding et al 2011), provide ample drill and practice with high rates of response (Hawkins et al 2017;Riccomini et al 2017), include immediate and corrective feedback (NMAP 2008), and incorporate an appropriate ratio of known to unknown facts (Riccomini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Mastery develops and strengthens as students practice responding correctly to math fact prompts (Fuchs et al 2008). Without immediate feedback, if students answer math fact items incorrectly, they may assume that their incorrect responses are correct and then risk becoming fluent with wrong answers (Hawkins et al 2017). In classrooms, teachers must ensure that all students receive immediate corrective feedback when practicing math facts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation